Implementasi Program Welijo Peduli Stunting Sebagai Upaya Pemberdayaan Masyarakat Di Wilayah Kerja Puskesmas Tongas (Studi Pada Desa Sumendi Kecamatan Tongas Kabupaten Probolinggo) - Marwiyah, Siti; Devi, Nourma Ulva Kumala; Jailani, Mahfudz (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
One of the problems that exist in society today is stunting, which is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Almost all regions of Indonesia have stunting problems, including Tongas Subdistrict, Probolinggo Regency, therefore it is necessary to empower the community to deal with the stunting problem. Therefore, the Tongas Health Center launched a stunting care welijo program which aims to empower the community to overcome the stunting problem in Tongas District, one of which is Sumendi Village. This study uses a qualitative descriptive method using the theory of policy implementation according to Van Meter and Van Horn (Anggara 2014, public policy) that there are six variables that influence the success of implementation, namely clear goals and standards, resources, quality of interorganizational relationships, characteristics of institutions/organizations. implementer, political, social, and economic environment, disposition. It was found that the implementation of the welijo care for stunting program in Sumendi Village has been going quite well, but the delivery of the welijo care stunting program is still hampered by the conditions of the political, social, and economic environment in Sumendi Village. Therefore, it is necessary for implementing agents to have the attitude and commitment to support the Welijo program for stunting so that it runs smoothly